2021
DOI: 10.1007/s10072-021-05087-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective cranial multineuritis in severe COVID-19 pneumonia: two cases and literature review

Abstract: Objective To report two cases of cranial multineuritis after severe acute respiratory syndrome caused by coronavirus-2. Methods Patients' data were obtained from medical records of the clinical chart of dell'Angelo Hospital, Venice, Italy. Results The first patient is a 42-year-old male patient who developed, 10 days after the resolution of coronavirus-2 pneumonia and intensive care unit hospitalization with hyperactive delirium, a cranial multineuritis with asymmetric distribution (bilateral hypoglossus invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Indeed, a recent post-mortem study clearly showed SARS-CoV-2 into the human olfactory neurons [ 9 ]. This result is in line with previous experimental works showing that the SARS-CoV-1 might reach the brain via olfactory nerves [ 23 ] and cranial neuritis possibly linked to a direct viral injury of the nervous structures through olfactory fibers was recently reported [ 24 ]. Notably, ACE2 was also observed into the human olfactory bulb [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, a recent post-mortem study clearly showed SARS-CoV-2 into the human olfactory neurons [ 9 ]. This result is in line with previous experimental works showing that the SARS-CoV-1 might reach the brain via olfactory nerves [ 23 ] and cranial neuritis possibly linked to a direct viral injury of the nervous structures through olfactory fibers was recently reported [ 24 ]. Notably, ACE2 was also observed into the human olfactory bulb [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Isolated or multiple cranial neuropathies not associated with polyneuropathy or other neurological disorders have been reported (Table 2). 93,96,111‐134 These included suspected bilateral olfactory neuropathy, 111,112 optic neuropathy, 113,114 oculomotor neuropathy either isolated 96,115,116,135 or associated with multiple cranial neuropathies, 93,128 unilateral 117‐124 or bilateral facial nerve palsy, 125‐127 sensorineural hearing loss, 129‐131 and lower cranial nerve impairment 132‐134 . Facial nerve palsy was the most commonly reported with 20 cases, followed by isolated oculomotor nerve neuropathy.…”
Section: Methodsmentioning
confidence: 99%
“…146 Three case of hypoglossal nerve neuropathy have been reported. [132][133][134] All occurred unilaterally and were temporally related with either endotracheal intubation or prone positioning, suggesting a iatrogenic etiology.…”
Section: Cranial Neuropathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing documentation that the autoimmune mechanism plays a crucial role in cranial neuropathy in COVID disease [20,21] The loss of smell is an early symptom that suggests COVID-19 disease explained by acute olfactory impairment which is characterized by the absence of nasal obstruction. [22] The imaging findings of cranial neuritis are suspicious when abnormal signal intensity with an increase in the size of the affected cranial nerves with postcontrast enhancement.…”
Section: Encephalitismentioning
confidence: 99%